Hormone replacement therapy in chronic active hepatitis; a case report. Issue 11 (November 1993) - Clements, D; Rhodes, J
Abstract : There is an increased incidence of osteoporosis in patients with chronic liver disease. Because patients with chronic active hepatitis (CAH) usually require corticosteroids for their liver disease prevention and treatment of bone loss presents a difficult problem. This case report describes a 41 year old female patient with CAH who had a high rate of bone loss. After an early menopause with noticeable menopausal symptoms, she was given transdermal oestrogen replacement therapy. The menopausal symptoms resolved completely, and there was no deterioration in her liver function tests or corticosteroid requirement. In addition, follow up quantitative bone mineral measurements over two years have shown improvement. This case shows the value of measurements of bone density, and oestrogen replacement therapy in CAH, even in the presence of continued corticosteroids.